The Age Threshold for Presidential Nominations in the Perspective of Dignified Justice Theory: Why is there a Mahkamah Keluarga Issue? - Bima, Muhammad Rinaldy; Jacob, John Tumba (Magister of Law, Faculty of Law, University of Mataram, 2023)
The Constitutional Court's decision regarding the age limit for nominations for President and Vice President has caused problems in society, one of which is related to the issue of the existence of a Family Court. This issue arises because juridically there is a logical inconsistency in the Constitutional Court's decision regarding the age limit for nominations for President and Vice President and related to the nomination of the President's children to contest the Presidential and Vice Presidential elections in the 2024 election. This research aims to analyze aspects of the age threshold for Presidential candidacy and The Vice President reviewed the theory of dignified justice along with an analysis of the Family Court issue as a result of the Constitutional Court's decision. This research is normative legal research which also orientates socio-legal aspects to assess the impact of a Constitutional Court Decision. The approach used is a conceptual and statutory approach. The research results confirm that the enigma of the age threshold for presidential candidacy in the perspective of the theory of dignified justice occurs because the Constitutional Court has gone beyond the open legal policy conception where the age threshold for presidential and vice presidential candidacy is actually the domain of the legislative institution as in the open legal policy conception. Judging from the theory of dignified justice, the enigma of the age threshold for presidential candidacy also occurs because the Constitutional Court failed to construct the dimensions of social justice as envisioned in the formulation of Pancasila. MK Decision on the Age of the President and Vice President as part of a legal product certainly has social, political and legal impacts on society. Issues related to the Family Court should be addressed wisely by the Constitutional Court because these issues exist as a form of public concern for the dignity of the Constitutional Court as an institution that protects the constitution.